2024
DOI: 10.1128/spectrum.02828-23
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of targeted carbapenemase genes and antibiotic susceptibility profiles among carbapenem-resistant Acinetobacter baumannii tested in the Antimicrobial Resistance Laboratory Network—United States, 2017–2020

Sarah Sabour,
Katie Bantle,
Amelia Bhatnagar
et al.

Abstract: Acinetobacter baumannii is a Gram-negative bacillus that can cause severe and difficult-to-treat healthcare-associated infections. A. baumannii can harbor mobile genetic elements carrying genes that produce carbapenemase enzymes, further limiting therapeutic options for infections. In the United States, the Antimicrobial Resistance Laboratory Network (AR Lab Network) conducts sentinel surveillance of carbapenem-resistant Acinetobacter baumannii (CRAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The value of surveilling local population structures remains to be determined, as the contribution of Ab phylogeny to pathogenesis and clinical outcomes is unclear. However, consistent with prior findings 28 , we observed that CR Ab lineages can harbor unique antimicrobial resistance features that may influence local medical practices. For example, OXA-23 has historically been the most prevalent carbapenamase among CR Ab and, thus, is a target of current and emergent rapid molecular detection tools in clinical labs 29 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The value of surveilling local population structures remains to be determined, as the contribution of Ab phylogeny to pathogenesis and clinical outcomes is unclear. However, consistent with prior findings 28 , we observed that CR Ab lineages can harbor unique antimicrobial resistance features that may influence local medical practices. For example, OXA-23 has historically been the most prevalent carbapenamase among CR Ab and, thus, is a target of current and emergent rapid molecular detection tools in clinical labs 29 .…”
Section: Discussionsupporting
confidence: 91%
“…However, we identified U.S. isolates belonging to CC2, CC108, and CC499 that display carbapenem resistance via other resistance determinants (i.e., OXA-24 or the FtsI A515V polymorphism), and the mechanism of carbapenem resistance among CC406 isolates remains to be identified 13,22 (Figure S4). During the preparation of this manuscript, Sabour, et al reported that carbapenemase gene content among CRAb differed by region, and these genes did not appear to always confer the same degree of resistance 28 . Though Sabour et al did not evaluate whether degree of carbapenem resistance was dependent on lineage, lineage-associated differences were observed previously 13 and in our study (i.e., OXA-23-associated IPM resistance was greater among CC2 isolates compared to CC250 isolates, Figure S2).…”
Section: Discussionmentioning
confidence: 96%